Reforma de pensiones en Chile: análisis de matching con diferencias en diferencias - Encina, Jenny (Estudios de Economía, 2013)
The present paper estimates the effect over participation outcomes of the new reform to the pension system made in Chile in 2008, using a difference in difference matching estimation. The main results found that the treated group shows a higher withdrawal from the labor market and that they worked an average of 8 percentage points (pp) fewer months than the control group in 2009. The treated group also contributed 18 pp fewer months than the control group, and they have, on average, 6 pp more months in inactive status. Looking at the difference in per capita income, the treated group has an average of US$34 more per month than the control group in 2009.